Luasnya Perlindungan Paten - Peter Mahmud Marzuki (Fakultas Hukum Universitas Islam Indonesia, 1999)
The Scope of patent protection has been determined by the interpretation on theprotec tion ofclaim. The study shows that if the protection concerns with the main invention which is described in theclaim, the protection will beso broad that it prevents other people to modify and develop technology: on the contrary, if the protection concerns with the wording for patented counter feiting which suf fersinjured for patent holder.